2014
DOI: 10.1007/978-3-662-44584-6_34
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Navigation on Multi-attributed Data Words

Abstract: Abstract. We study temporal logics and automata on multi-attributed data words. Recently, BD-LTL was introduced as a temporal logic on data words extending LTL by navigation along positions of single data values. As allowing for navigation wrt. tuples of data values renders the logic undecidable, we introduce ND-LTL, an extension of BD-LTL by a restricted form of tuple-navigation. While complete ND-LTL is still undecidable, the two natural fragments allowing for either future or past navigation along data valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 27 publications
(63 reference statements)
1
41
0
Order By: Relevance
“…These are finite words in which every position carries a label from a finite alphabet and a finite tuple of data values from some infinite alphabet. A wealth of specification formalisms for data words (and slight variants) have been introduced stemming from automata to adequate logical languages such as first-order logic [Bojańczyk et al 2011;Schwentick and Zeume 2012] and temporal logics [Figueira 2010;Decker et al 2014].…”
Section: Encoding Data Words With Multiple Attributesmentioning
confidence: 99%
“…These are finite words in which every position carries a label from a finite alphabet and a finite tuple of data values from some infinite alphabet. A wealth of specification formalisms for data words (and slight variants) have been introduced stemming from automata to adequate logical languages such as first-order logic [Bojańczyk et al 2011;Schwentick and Zeume 2012] and temporal logics [Figueira 2010;Decker et al 2014].…”
Section: Encoding Data Words With Multiple Attributesmentioning
confidence: 99%
“…These cases can, however, be handled by additional constraints added to ϕ. Data words over a thus obtained partially ordered attribute set of depth k can now be encoded into words over the linear ordering [k] of equal depth k. The idea is to encode a single position into a frame of positions in the fashion of [KSZ10, DHLT14]. That way a single attribute on every level suffices.…”
Section: From Ltl ↓ Tqo To Ncs and Backmentioning
confidence: 99%
“…PLRV LRV PLRV = CLTL XF,XF −1 [DDG12] LRV = CLTL XF [DDG12] (1 attribute) Figure 1: Placing LRV and variants in the family of data logics two fragments BD-LTL − and BD-LTL + of that richer logic have been introduced and shown to admit 2expspace-complete satisfiability problems. Forthcoming logic LRV is shown in [DHLT14] to be strictly less expressive than BD-LTL + .…”
Section: Introductionmentioning
confidence: 99%
“…Note that in [KSZ10], a richer logic BD-LTL has been introduced and it has been shown that satisfiability is equivalent to the reachability problem for Petri nets. Moreover, in [DHLT14], BD-LTL [KSZ10] (≡ Reach(VASS)) LTL ↓ 1 (X, X −1 , U, S) [DL09] (undec.) PLRV LRV PLRV = CLTL XF,XF −1 [DDG12] LRV = CLTL XF [DDG12] (1 attribute) Figure 1: Placing LRV and variants in the family of data logics two fragments BD-LTL − and BD-LTL + of that richer logic have been introduced and shown to admit 2expspace-complete satisfiability problems.…”
Section: Introductionmentioning
confidence: 99%